Estudo dos impactos gerados pelas tecnologias sociais de gestão hídrica sobre a sustentabilidade do pequeno agricultor no semiárido cearense: o caso dos municípios de Cariús e Saboeiro - Santos, Kelvio Felipe dos (2013)
Public actions must act in the process of social and economic development in order to make this a more symmetric process. But in poor regions, poorly designed public policies tend to deepen the social exclusion model. In this context, this study aims to analyze the impacts generated by social technologies of water management on the sustainability of small farmers in the semiarid region of Ceará. These social technologies of water management are intended to offer alternatives for capture, storage and use of rain water for both human consumption but also for use in agriculture by building tanks, thereby improving the living with the effects of drought. To achieve the objective of the study was a survey of primary data, with the application of 150 questionnaires between beneficiaries and non-beneficiaries of the program in the municipalities of Carius/CE and Saboeiro/CE. The analysis of the impact of social technologies was through the construction of indices with unmatched data and the application of 'propensity score matching model', which aims to pair the data. The study reported in both paired and unpaired fashion, that social technologies of water management are generating a positive impact on the sustainability of its beneficiaries in the semiarid region of Ceará, in general, as they have the ability to generate agricultural income in the same period of drought returning this production to organic sense and reducing harm to the environment.